(untitled) (Research, Society and Development, 2022)
Introduction: Dietary adequacy in people living with HIV/AIDS improves levels of CD4 T lymphocytes and intestinal absorption, minimizes muscle loss and symptoms of infection. Objective: Conduct a survey of food consumption and quality of life of PLWHA in the Northern Region of Brazil. Method: Cross-sectional analytical observational study with a random sample of 77 patients of both sexes, aged between 20 and 63 years, carried out between September 2021 and April 2022, at the Specialized Care Service (SAE), Hospital Universitário João de Barros Barreto from the Federal University of Pará. The food survey was carried out using the Food Frequency Questionnaire (FFQ). The habits that interfere in the healthy life of PLWHA were studied through the lifestyle survey. Results: Of the patients who participated in the research (n=77, 100%), 64.93% (n=50) were men and 35.06% (n=27) were women. The results of the Food Survey through the FFQ showed that food consumption was expressive of energy foods, however, with a low intake of industrialized foods. The consumption of vegetables was below the indicated parameters. Regarding quality of life, 50% of men and 55% of women were sedentary and most had smoking and drinking habits, since 27% of men and 37% of women were smokers and drinkers. Conclusion: There was a considerable frequency of sedentary, smokers, alcoholics and inadequate consumption of healthy foods. A healthy diet and life habits are fundamental in promoting the improvement of the quality of life of PLWHA.